Development of an interactive multimedia-CBT-program for dental implantology and using tests of a program prototype - Schuhbeck, Michael; Haßfeld, Stefan; Koke, Ulrich; Mühling, Joachim (European journal of dental education, 1999)
The aim of the study was the development of a teaching program for dental implantology designed to improve student education as well as further training in this area. Initially, the computer equipment of German dentists was evaluated. Then, the contents of a teaching program “implantology interactive” were defined. A fully functional program prototype was developed in cooperation with a medical publishing house. Subsequently, the program was tested and statistically evaluated by 70 dental students and 40 dentists for the purpose of quality assurance.
First published: 20 January 2011
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 19.02.2021